Respuesta :

Answer:

A. (1, 2) and (4, 3)

B. Slope (m) = ⅓

C. y - 2 = ⅓(x - 1)

D.[tex] y = \frac{1}{3}x + \frac{5}{3} [/tex]

E. [tex] -\frac{1}{3}x + y = \frac{5}{3} [/tex]

Step-by-step explanation:

A. Two points on the line from the graph are: (1, 2) and (4, 3)

B. The slope can be calculated using two points, (1, 2) and (4, 3):

[tex] slope (m) = \frac{y_2 - y_1}{x_2 - x_1} = \frac{3 - 2}{4 - 1} = \frac{1}{3} [/tex]

Slope (m) = ⅓

C. Equation in point-slope form is represented as y - b = m(x - a). Where,

(a, b) = any point on the graph.

m = slope.

Substitute (a, b) = (1, 2), and m = ⅓ into the point-slope equation, y - b = m(x - a).

Thus:

y - 2 = ⅓(x - 1)

D. Equation in slope-intercept form, can be written as y = mx + b.

Thus, using the equation in (C), rewrite to get the equation in slope-intercept form.

y - 2 = ⅓(x - 1)

3(y - 2) = x - 1

3y - 6 = x - 1

3y = x - 1 + 6

3y = x + 5

[tex] y = \frac{1}{3}x + \frac{5}{3} [/tex]

E. Convert the equation in (D) to standard form:

[tex] y = \frac{1}{3}x + \frac{5}{3} [/tex]

[tex] -\frac{1}{3}x + y = \frac{5}{3} [/tex]